Agile risk management - Moran, Alan (New York : Springer, 2014)
This book elucidates the principles of agile risk management and describes how these relate to individual projects. It also proposes an agile risk-management process derived from classical risk management but adapted to the circumstances of agile projects.
Includes bibliographical references (pages 97-101).
hza 08/01/2019, ijb, 29/01/2019
Loans
Keywords: Agile software development; Risk management; Software engineering; Computer science; System safety; Management information systems; Project management; Quality control